Improving Initial Medication Adherence to cardiovascular disease and diabetes treatments in primary care: Pilot trial of a complex intervention - Corral-Partearroyo, Carmen; Sánchez-Viñas, Alba; Gil-Girbau, Montserrat; Peñarrubia-María, María Teresa; Aznar-Lou, Ignacio; Serrano-Blanco, Antoni; Carbonell-Duacastella, Cristina; Gallardo-González, Carmen; Olmos-Palenzuela, Maria del Carmen; Rubio-Valera, Maria (Frontiers in Public Health, 2022)
Introduction: The Initial Medication Adherence (IMA) intervention is a multidisciplinary and shared decision-making intervention to improve initial medication adherence addressed to patients in need of new treatments for cardiovascular diseases and diabetes in primary care (PC). This pilot study aims to evaluate the feasibility and acceptability of the IMA intervention and the feasibility of a cluster-RCT to assess the effectiveness and cost-effectiveness of the intervention. Methods: A 3-month pilot trial with an embedded process evaluation was conducted in five PC centers in Catalonia (Spain). Electronic health data were descriptively analyzed to test the availability and quality of records of the trial outcomes (initiation, implementation, clinical parameters and use of services). Recruitment and retention rates of professionals were analyzed. Twenty-nine semi-structured interviews with professionals (general practitioners, nurses, and community pharmacists) and patients were conducted to assess the feasibility and acceptability of the intervention. Three discussion groups with a total of fifteen patients were performed to review and redesign the intervention decision aids. Qualitative data were thematically analyzed. Results: A total of 901 new treatments were prescribed to 604 patients. The proportion of missing data in the electronic health records was up to 30% for use of services and around 70% for clinical parameters five months before and after a new prescription. Primary and secondary outcomes were within plausible ranges and outliers were barely detected. The IMA intervention and its implementation strategy were considered feasible and acceptable by pilot-study participants. Low recruitment and retention rates, understanding of shared decision-making by professionals, and format and content of decision aids were the main barriers to the feasibility of the IMA intervention. Discussion: Involving patients in the decision-making process is crucial to achieving better clinical outcomes. The IMA intervention is feasible and showed good acceptability among professionals and patients. However, we identified barriers and facilitators to implementing the intervention and adapting it to a context affected by the COVID-19 pandemic that should be considered before launching a cluster-RCT. This pilot study identified opportunities for refining the intervention and improving the design of the definitive cluster-RCT to evaluate its effectiveness and cost-effectiveness. Trial registration: ClinicalTrials.gov, NCT05094986.